Orientasi Kewirausahaan dan Inovasi Produk pada Kinerja Bisnis UMKM Kopi di Lahat - Indra Hartini; Iskandar Iskandar; Emila Sholiha (Journal of Management and Bussines (JOMB), 2023)
This research aims to develop a scientific discussion of inconsistent findings regarding the influence of entrepreneurial orientation on product innovation. The research method uses the Purposive Sampling method with a questionnaire distributed online. Data were analyzed using the Partial Least Square Structural Equation Model (PLS-SEM) used to test three hypotheses. The results of this research prove that entrepreneurial orientation increases product innovation. Conclusion, Product innovation has a positive effect on business performance. Entrepreneurial orientation and innovation simultaneously improve business performance, product innovation mediates the positive relationship between entrepreneurial orientation and business performance. Keywords: Product Innovation, Business Performance, Entrepreneurship Orientation